TEN YEARS OF PRESIDENT JOKO WIDODO'S LEADERSHIP FORGING A DOMINANT NATIONAL LEGACY: SEPULUH TAHUN KEPEMIMPINAN PRESIDEN JOKO WIDODO MENANCAPKAN LEGACY NASIONAL YANG DOMINAN - Rizza, Shofa Zulfikar; Kurniawan, Anfal (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2024)
This article examines Joko Widodo's ten years in office in Indonesia with a focus on key policies and their impact on society. It begins with the need to understand the social and economic transformation that has taken place under Jokowi's administration, as well as the challenges faced by the country. Initially, Jokowi was known as a populist leader as he showed his simplicity in living his life. However, politics can take a different course. The presidential term in Indonesia lasts for five years in one term and can be re-elected for one more term. Based on Article 7 of the 1945 Constitution. This means that the leadership era of President Joko Widodo or familiarly known as Jokowi is coming to an end, because he has been in power for two periods or the equivalent of ten years. The issues raised include how the implemented policies contribute to economic growth, infrastructure, and social welfare, as well as the community's response to these policies. The purpose of this study is to analyze the impact of government policies and evaluate Jokowi's leadership performance in the political and social context. The results show that despite significant progress in infrastructure development and poverty reduction, there are still major challenges in terms of uneven development and human rights issues that need to be addressed to build a more inclusive future for Indonesia.